1996
DOI: 10.1046/j.1464-410x.1996.09815.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐controlled monitoring of bladder pressure in the prevention of ‘TUR syndrome’: a randomized study of 53 cases

Abstract: The continuous computerized monitoring of bladder pressure during TURP effectively reduced the absorption of irrigant fluid, making the procedure safer for the patient and easier for the surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Thus intravesical pressure is probably the pre‐eminent factor determining fluid absorption. This contention is supported by the good results of TURP using computer‐controlled monitoring of bladder pressure [ 19]. Continuous intravesical pressure monitoring during TURP in the present study showed clear differences, despite the continuous removal of fluid, suggesting that the Iglesias technique cannot be defined as a ‘low pressure’ TURP.…”
Section: Discussionsupporting
confidence: 62%
“…Thus intravesical pressure is probably the pre‐eminent factor determining fluid absorption. This contention is supported by the good results of TURP using computer‐controlled monitoring of bladder pressure [ 19]. Continuous intravesical pressure monitoring during TURP in the present study showed clear differences, despite the continuous removal of fluid, suggesting that the Iglesias technique cannot be defined as a ‘low pressure’ TURP.…”
Section: Discussionsupporting
confidence: 62%
“…Several authors have found irrigation using the suprapubic trocar to be efficient, 65 while others have not. There is even more widespread scepticism about the effectiveness of the Iglesias method.…”
Section: Low-pressure Irrigationmentioning
confidence: 99%
“…A pressure warning device may remind the surgeon to empty the bladder in time or to control the system in cases where continuous irrigation is used. However, the height of the fluid bag over the bladder is of no consequence as long as only a volume corresponding to the almost horizontal first phase of the bladder pressure curve is used [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The resection is then resumed with more frequent emptying of the bladder to keep the pressure in the operating field below the assumed pressure in the veins (in case of IVA). The amount of bladder capacity that may be used is basically determined by the bladder compliance [8,9]. Just before the flow in the irrigating jet is beginning to decline (as a sign of rising pressure) the bladder is usually emptied.…”
Section: Methodsmentioning
confidence: 99%